2010
DOI: 10.1007/s12640-010-9167-1
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Vanadium-Mediated Developmental Hypomyelination Is Related to Destruction of Oligodendrocyte Progenitors Through a Relationship with Ferritin and Iron

Abstract: The second post-natal week in rat is the period of the most intense oligodendrocyte development and myelination. This period coincides with peak iron import by oligodendrocytes. During that time oligodendrocyte progenitors (OPCs) are sensitive to agents that may disturb normal iron homeostasis and assimilation of iron into these cells. One mechanism by which iron homeostasis can be disrupted is by environmental exposure to other metals. Vanadium is a transition metal, and exposure to vanadium during early brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 36 publications
3
36
1
Order By: Relevance
“…The decrease in NO bioavailability has been associated with hypertension and derangement in vascular endothelium [28,29]. From the present study, the rats did not recover from the reduced tissue NO bioavailability.…”
Section: Discussioncontrasting
confidence: 71%
“…The decrease in NO bioavailability has been associated with hypertension and derangement in vascular endothelium [28,29]. From the present study, the rats did not recover from the reduced tissue NO bioavailability.…”
Section: Discussioncontrasting
confidence: 71%
“…Vanadium-induced astrogliosis has previously been reported in the cerebellum and hippocampus of adult rats exposed to sodium metavanadate for 5 days (Garcia et al, 2005) indicating a rapid response of astrocytes to this challenge. Astrocyte activation was also observed in the hippocampus and corpus callosum after vanadium exposure in rats of 2 weeks of age (Olopade and Connor, 2011; Todorich et al, 2011) and 3-week-old mice (Mustapha et al, 2014), indicating that reactive astrogliosis is a component of vanadium neurotoxicity. In the present study astrocytic response was observed at the onset of the exposure increasing till 12 months but with increasing vanadium exposure into old age, this response decreased.…”
Section: Discussionmentioning
confidence: 98%
“…Our interest in DNA repair genes rest in the evidence that their expression is a good indicator of oxidative stress (Powel et al 2005) and metals have well known oxidative, neurotoxic, neurodevelopmental and neurobehavioral effects (Barth et al 2002; Colin-Barenque et al 2008; Afeseh-Ngwa et al 2011; Todorich et al 2011; Winneke 2011;Yen et al 2011;Martinez et al 2011). Repair enzymes recognize and remove DNA adducts, correct the DNA sequence and rejoin strand breaks.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative damage to frontal lobes in this young urbanite cohort poses a significant cause for concern in terms of developmental and cognitive effects (Barth et al 2002; Burton and Guilarte 2009; Guilarte 2010; Martinez et al 2011;Todorich et al 2011;Winneke 2011). …”
Section: Discussionmentioning
confidence: 99%